(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This article proceeds from a central problematic concerned with the nature of the relationship between the historical development of the Moroccan university and the legal framework governing it, on the one hand, and the manifestations of the educational crisis it continues to face, on the other. Building on this problematic, the article seeks to shed light on the various difficulties and challenges that still confront the Moroccan university, to analyse the forms through which this crisis is expressed, and to examine its repercussions for the university system in light of the limitations of the legal framework that regulates it. To this end, the article is structured around three interrelated and complementary sections. The first section is devoted to the historical context in which the university as an institution emerged and developed. The second examines the trajectories of the Moroccan university’s development and the consequences they have produced. The third section, in turn, focuses on the structural and pedagogical challenges that continue to face the Moroccan university, as well as the ways in which these challenges have contributed to the deepening of the educational crisis that characterises Morocco’s university system. The article concludes that the Moroccan university continues to suffer from dysfunctions at multiple levels, adversely affecting both its performance and its capacity to fulfil its expected roles and functions. This situation is largely attributable to the marked intensification of the educational crisis within the university system, itself the result of the failure of the reforms undertaken in higher education from the mid-1970s to the present day.